Influence of genetic improvement in beef sheep flocks (Research, Society and Development, 2020)
The objective of this work was to compare the morphometric measurements of pure sheep of origin of the Santa Inês and Dorper breeds with the measurements of the sheep resulting from their crossing in the Paraíba hinterland, to characterize To characterize the sheep in that region or the sheep raised in the hinterland and show the importance of having genetic improvement in these herds. 200 animals were used, being 50 pure Santa Inês sheep, 50 pure Dorper and 100 crossbred Santa Inês x Dorper animals. Body length (WC), anterior height (AA) and posterior height (AP) measurements were collected. The data were tabulated in the Microsoft Excel 2016® program and analyzed using the one-way Analysis of Variance (ANOVA) test, and the means were compared using the Tukey test at a significance level of 5%. It was found that elite animals have morphometric measurements much higher than SRD animals reared in the Paraíba hinterland, with CC being the most differentiated measure, so they need the introduction of good genetic material as well as instruction to rural producers on the selection that must be made in their herds to increase productivity.